Cervical cancer with paraaortic involvement: do patients truly benefit from tailored chemoradiation therapy? A retrospective study on 8 French centers. (October 2015) - Chantalat, Elodie; Vidal, Fabien; Leguevaque, Pierre; Lepage, Benoît; Mathevet, Patrice; Deslandres, Marion; Motton, Stéphanie
Abstract: We retrospectively studied the therapeutic significance of extended-field radiotherapy combined with concurrent platinum-based chemotherapy for the management of cervical carcinoma with paraaortic spread. Treatment response and survival outcomes were evaluated. One hundred and fifteen women were retrospectively studied. Radiological staging was conducted in 101 (87.8%) patients and paraaortic lymphadenectomy in 78 (67.8%). Patterns of treatment comprised chemoradiation therapy (100%), intracavitary brachytherapy (81.7%), completion surgery (60%) and neoadjuvant chemotherapy (4.3%). Four-year overall and disease-free survivals were 32.7% and 28.8%, respectively. Progression and relapse mostly involved the locoregional area and distant organs, rather than the paraaortic area. Advanced FIGO stage at baseline was the most significant prognostic factor (HR = 3.02, p = 0.01). Despite systematic extended-field chemoradiation therapy, paraaortic involvement in cervical cancer is associated with poor survival outcomes. The patterns of progression and recurrence suggest the existence of occult metastatic disease at presentation. Additional systemic treatment might thus be beneficial.